Aggression Among Athletes: An Asian versus American Comparison - Ferraro, T. (Athletic Insight - The Online Journal of Sport Psychology, 1999)
This paper presents an analysis of the differences between Asian and American athletes. Using questionnaire data from Asia and the U.S. , the author suggests that Asian athletes tend to be more perfectionistic, more work oriented, receive more family support, are more family oriented and tend to be less aggressive and less angry. Conversely, the American athlete appears to be more aggressive, less work-oriented, often complains more about practice, have looser family ties, and are less guilty about defeating opponents.